Information and Communication Technology Application and the Provision of Reference Services in Selected University Libraries in Western Uganda. - Nabukenya, Judith (Kabale University, 2024)
The study focused on ICT applications and the provision of reference services at Bishop Stuart University, Kabale University and Mbarara University of Science and Technology in western Uganda with aim of finding better strategies for improving reference service provisions in university libraries. The study was guided by four specific objectives: To identify ICT platforms available, to determine reference services, find out challenges encountered while applying ICT and propose strategies to challenges encountered when applying ICTs in libraries in Western Uganda. The study employed a descriptive cross-sectional survey research design while utilizing a mixed research approach .Questionnaires and interviews were used to collect data. The findings revealed that these findings indicated the varying usage of different ICT platforms by librarians for reference services across the three universities. Specifically: WhatsApp was the most frequently used platform, with 65% (34 respondents) using it, Email was the second most used, with 46% (24 respondents), Websites are the third most used. The findings highlighted the major challenges librarians face when applying different ICT platforms in reference services at the selected universities. Inadequate power supply is the most significant challenge, reported by 71% (37 respondents).The study recommended that, given less used platforms like Myspace, web forms and RSS libraries should focus on providing continuous training and support for these and other emerging ICT platforms. Keywords: Information and Communication Technology, Reference services, Universities, Western Uganda, ICT platforms, ICT services.